If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x+6)(x+2)=0
We multiply parentheses ..
(+2x^2+4x+6x+12)=0
We get rid of parentheses
2x^2+4x+6x+12=0
We add all the numbers together, and all the variables
2x^2+10x+12=0
a = 2; b = 10; c = +12;
Δ = b2-4ac
Δ = 102-4·2·12
Δ = 4
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{4}=2$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(10)-2}{2*2}=\frac{-12}{4} =-3 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(10)+2}{2*2}=\frac{-8}{4} =-2 $
| n/3+12=15 | | -4d+4=-3+3d | | 10=w+2 | | (x+12)(x+4)=0 | | -4d+4=-33d | | 5(x-3)+8=3(-1+x) | | 4(x-1)+x+8=3x-2 | | -6+7j=10+9j | | -8+8z+6=8+7z | | x2=108. | | (2x+12)(2x+4)=0 | | (2x+7)(2x+4)=0 | | 10+8f=10f | | 3/4m=17 | | -7h-6=2-8h | | x2=45. | | 7b-2=8+6b | | (3x)+4=5 | | 3x÷4=2.5x | | 5e-7=18 | | -8w-10=-3w | | 54=x | | 3x-8=-7x | | -8+2d=4d | | x-15/5=27 | | 3x-4=2.5× | | -2q+7=-q | | 148-u=215 | | -10m-10=-9m | | -2.3+y/5=-14.8 | | -5h-2=-6h | | 5-2k=-3k |